Mentoring that matters: African graduate students’ perceptions of faculty mentorship during transition - Ngbabare, Susan M. J. (Journal of International Students, 2025)
This study explores the perceptions of African graduate students in the United States regarding faculty mentorship, utilizing the framework of Appreciative Inquiry (AI). This research aims to understand how AI, which focuses on strengths, resilience, and positive experiences, can enhance the mentorship experience of African students during their transition into U.S. academic, cultural, and social systems. Through qualitative analysis of in-depth interviews with 13 graduate students, the study reveals five interrelated themes: recognition of student strengths, cultural inclusivity, constructive feedback, emotional support, and development of self-efficacy. While AI revealed mentoring practices that empowered students, the findings also highlight institutional inconsistencies and systemic barriers that limited equitable mentorship experiences. The study concludes with implications for policy and practice, recommending that universities institutionalize culturally responsive, strength-based mentorship programs embedded within broader equity frameworks.